2018
DOI: 10.3892/ijo.2018.4523
|View full text |Cite
|
Sign up to set email alerts
|

Human non‑small cell lung cancer cells can be sensitized to camptothecin by modulating autophagy

Abstract: Lung cancer is a prevalent disease and is one of the leading causes of mortality worldwide. Despite the development of various anticancer drugs, the prognosis of lung cancer is relatively poor. Metastasis of lung cancer, as well as chemoresistance, is associated with a high mortality rate for patients with lung cancer. Camptothecin (CPT) is a well-known anticancer drug, which causes cancer cell apoptosis via the induction of DNA damage; however, the cytotoxicity of CPT easily reaches a plateau at a relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…As NSCLC cells depleted of COMMD4 were hypersensitive to irradiation, we next investigated whether COMMD4 depletion might also enhance sensitivity to camptothecin in NSCLC cells. Camptothecin class of compounds have shown promise in the treatment of many cancers including NSCLC 38 and function by generating cytotoxic single-strand DNA breaks that are processed into DNA double-strand breaks during the S-phase of the cell cycle. 39 While we observed no difference in the sensitivity between control and COMMD4 siRNA-depleted HBEC3-KT cells (Fig.…”
Section: Commd4 Depletion Induces Mitotic Catastrophe In Nsclc Cellsmentioning
confidence: 99%
“…As NSCLC cells depleted of COMMD4 were hypersensitive to irradiation, we next investigated whether COMMD4 depletion might also enhance sensitivity to camptothecin in NSCLC cells. Camptothecin class of compounds have shown promise in the treatment of many cancers including NSCLC 38 and function by generating cytotoxic single-strand DNA breaks that are processed into DNA double-strand breaks during the S-phase of the cell cycle. 39 While we observed no difference in the sensitivity between control and COMMD4 siRNA-depleted HBEC3-KT cells (Fig.…”
Section: Commd4 Depletion Induces Mitotic Catastrophe In Nsclc Cellsmentioning
confidence: 99%
“…This indicates the participation of autophagy in the development of MDR. Prosurvival role of autophagy was also confirmed in breast, ovarian, esophageal, lung, prostate, renal and pancreatic cancers [98,99,100,101,102,103,104]. Similar effect was observed in the case of glioma and bladder cancer [106,107].…”
Section: Autophagy In Multidrug Resistancementioning
confidence: 70%
“…As MDR is responsible for most of the chemotherapy failures, its inhibition would be of great importance for oncological patients [97]. Recent literature reports indicate the process of autophagy may, in at least some cases, be the basis of MDR, but the relationship between these phenomena is still not fully understood [98,99,100,101,102,103,104]. Like in the initiation and progression of cancer also in the case of MDR, the role of autophagy may be twofold.…”
Section: Autophagy In Multidrug Resistancementioning
confidence: 99%
“…Recent studies reported that dovitinib showed antitumor activity by inhibiting cell proliferation and inducing apoptosis in breast and colorectal cancer cells [31, 32]. However, accumulated studies suggest that autophagy induces chemoresistance against chemotherapeutic agents by inhibiting apoptosis of cancer cells [33]. Our prior finding showed that dovitinib increased autophagy in various breast cancer cells, and the antitumor effect of dovitinib could be restricted by autophagic cell death.…”
Section: Resultsmentioning
confidence: 96%